Banking Union and the governance of credit institutions: A legal perspective - Jens-Hinrich Binder (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The creation of the Banking Union is likely to come with substantial implications for the governance of Eurozone banks. The European Central Bank, in its capacity as supervisory authority for systemically important banks, as well as the Single Resolution Board, under the EU Regulations establishing the Single Supervisory Mechanism and the Single Resolution Mechanism, have been provided with a broad mandate and corresponding powers that allow for far-reaching interference with the relevant institutions' organisational and business decisions. Starting with an overview of the relevant powers, the present paper explores how these could - and should - be exercised against the backdrop of the fundamental policy objectives of the Banking Union. The relevant aspects directly relate to a fundamental question associated with the reallocation of the supervisory landscape, namely: Will the centralisation of supervisory powers, over time, also lead to the streamlining of business models, corporate and group structures of banks across the Eurozone?
Keywords: G15; G21; G28; K22; K23; 330; Banking Union; Single Supervisory Mechanism; Single Resolution Mechanism; Banking Regulation; Bank Corporate Governance